1993
DOI: 10.1590/s0004-282x1993000100002
|View full text |Cite|
|
Sign up to set email alerts
|

Histopathological and immunohistochemical study of the brain and heart in the chronic cardiac form of Chagas' disease

Abstract: A histopathological and immunohistochemical study of the brain and heart was made in 50 patients with the chronic cardiac form of Chagas' disease. The immunohistochemical technique used was the peroxidase-antiperoxidase method adapted for the demonstration of the T. cruzi amastigotes. Histological and immunohistochemical examination of the brain showed encephalitis in multiple foci, although sparse, in four patients (8%). In one of the patients the process was recent, active, and containing parasites. In the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
0
18
0
2
Order By: Relevance
“…Although necropsy studies report a high frequency of embolic events [6,7] the long-term risk of stroke has not been fully determined. A clinical study with a cohort of patients with mild to moderate heart failure due to Chagas disease reported a stroke frequency of 1.2% during the first year of follow-up [8].…”
Section: Incidence Of Ischemic Cerebrovascular Events In Chagas Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Although necropsy studies report a high frequency of embolic events [6,7] the long-term risk of stroke has not been fully determined. A clinical study with a cohort of patients with mild to moderate heart failure due to Chagas disease reported a stroke frequency of 1.2% during the first year of follow-up [8].…”
Section: Incidence Of Ischemic Cerebrovascular Events In Chagas Diseasementioning
confidence: 99%
“…Previous studies have shown that stroke may be the first manifestation of this disease, regardless of systolic dysfunction or presence of cardiac arrhythmias. In contrast to autopsy studies, which report a high frequency of cerebral infarction [6,7], clinical studies have demonstrated a low prevalence of stroke in patients with chronic Chagas heart disease [8].…”
Section: Introductionmentioning
confidence: 96%
“…7 Heart-related diseases in CD includes cardiomegaly, dysrhythmia, heart failure, and sudden cardiac death. 8 Pathologic studies of the brain have shown cerebral infarction in 9.4% and 26.3% 9,10 of patients with the chronic form of CD. Previous studies described a predominant cardioembolic cause of ischemic stroke in CD.…”
mentioning
confidence: 99%
“…Acute disease has been reported to cause tumor-like masses of polymorphous chronic granulomatous inflammation in the central nervous system in immunocompromised individuals [10][11][12][13]. As the patient traveled to Mexico 5 months prior to presentation, it is possible that he was infected with T. cruzi during that trip and developed an acute form of Chagas' disease in the subsequent months, although an incubation time of 5 months is longer than expected.…”
Section: Discussionmentioning
confidence: 99%